(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
The article analyzes the importance of family stability and intergenerational succession. The transmission of traditional values from generation to generation is considered an important factor for the strength of the family institution. The educational process, cultural heritage, and social norms are formed through family succession. The strength of the connection between generations also affects the stability of society. The results of the study show that the preservation of family values serves social development.